Lack of association of iron metabolism and Dupuytren's disease - Hnanicek, J; Cimburova, M; Putova, I; Svoboda, S; Stritesky, J; Kratka, K; Sosna, B; Horak, J (Journal of the European Academy of Dermatology and Venereology, 2008)
BACKGROUND: Iron accumulation as seen in genetic haemochromatosis is a major cause of hepatic fibrogenesis. A link between chronic liver disease and Dupuytren's disease (DD) is well established, especially in alcoholics. AIM: The aim of the present study was to test the hypothesis that iron accumulation might cause fibrosis of the palmar aponeurosis leading to DD. PATIENTS AND METHODS: We examined iron metabolism, mutations of the HFE gene, serum cholesterol, alcohol consumption, presence of chronic liver disease, diabetes and history of severe manual work in a group of 90 patients who had undergone surgery for a severe form of DD. The tissue removed during surgery was histologically examined to confirm the diagnosis of DD. For a control group, we used 33 healthy subjects with similar profiles. RESULTS: The DD group consisted of 82 men and 8 women. Chronic liver disease was found in 27% of DD patients, compared with 6.1% of control subjects (P = 0.013). A history of hand traumatization was present in 33% of DD patients vs. 15% of control subjects (P = 0.048). Excessive alcohol consumption was present in 35.5% of DD patients compared with 15.1% of controls (P = 0.029). None of the other tested parameters, including the prevalence of HFE gene mutations, showed a significant difference between the two groups. CONCLUSIONS: Iron accumulation does not play a major role in the pathogenesis of DD. However, sex, age, manual labour and alcohol consumption are risk factors for progression of DD. We observed a high incidence of chronic liver disease in patients with DD.
Keywords: železo; Cholesterol; Humans; Iron; Dupuytrenova kontraktura; cholesterol; lidé středního věku; Hemochromatosis; Alcohol Drinking; Liver Diseases; pití alkoholu; Female; mutace; rizikové faktory; dospělí; Aged; senioři; lidé; zaměstnání; Occupations; Diabetes Mellitus; Adult; nemoci jater; ženské pohlaví; Male; Middle Aged; Dupuytren Contracture; hemochromatóza; Aged, 80 and over; senioři nad 80 let; Mutation; mužské pohlaví; diabetes mellitus; Risk Factors